Lessons Learned from CO2 Injection, Monitoring, and Modeling Across a Diverse Portfolio of Depleted Closed Carbonate Reef Oil Fields – The Midwest Regional Carbon Sequestration Partnership Experience. (July 2017) - Gupta, Neeraj; Kelley, Mark; Place, Matt; Cumming, Lydia; Mawalkar, Sanjay; Srikanta, Mishra; Haagsma, Autumn; Mannes, Robert; Pardini, Rick
Abstract: The MRCSP Michigan Basin Large-Scale Injection Project is evaluating CO2 storage and utilization in a complex of closed reservoirs at various stages of production and enhanced oil recovery (EOR) life-cycle. Since 2013, MRCSP has successfully injected and monitored the net storage of more than 600, 000 metric tons of CO2 out of the goal of 1 million metric tons. A number of monitoring technologies have been tested, and various modeling approaches are being applied to evaluate CO2 migration, injectivity, capacity, and containment.